2020
DOI: 10.1021/acsomega.9b03526
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for Sandstone Acidizing Using in Situ-Generated Hydrofluoric Acid with the Aid of Thermochemicals

Abstract: In this study, an in situ-generated hydrofluoric acid (HF) was used for sandstone acidizing, where an acid precursor (ammonium fluoride NH 4 F) reacted with a suitable oxidizer (sodium bromates NaBrO 3 ) in an exothermic reaction. First, the new chemical mixture was prepared to react with pure quartz samples and the reaction effluent was analyzed to identify the presence of Si + ions using the inductively coupled plasma (ICP) technique. Core flooding experiments were performed using Gray Berea sandstone cores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This was due to the creation of etched surfaces during thermochemical fracturing. Gomaa et al [ 17 , 18 ] found similar results in terms of permeability improvement in different sandstone rocks with a variety of clay contents.…”
Section: Introductionmentioning
confidence: 73%
“…This was due to the creation of etched surfaces during thermochemical fracturing. Gomaa et al [ 17 , 18 ] found similar results in terms of permeability improvement in different sandstone rocks with a variety of clay contents.…”
Section: Introductionmentioning
confidence: 73%
“…Upon application of this new stimulation technology, the true production potential of sandstone reservoirs can be achieved, well tubular corrosion will be minimized, and handling hazardous chemicals such as HF will be avoided. 28 Zhao synthesized a series of cationic Gemini surfactants with different hydrophobic chain lengths (C n -4-C n , n = 12, 14, 16). The surface tension, adhesion work, and AFM are used to investigate the effect of hydrophobic chain length and concentration of surfactant on surface activities adsorption morphology and adsorption capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Gomaa used an in situ-generated hydrofluoric acid (HF) for sandstone acidizing, where an acid precursor (ammonium fluoride NH 4 F) reacted with a suitable oxidizer (sodium bromates NaBrO 3 ) in an exothermic reaction. Upon application of this new stimulation technology, the true production potential of sandstone reservoirs can be achieved, well tubular corrosion will be minimized, and handling hazardous chemicals such as HF will be avoided . Zhao synthesized a series of cationic Gemini surfactants with different hydrophobic chain lengths (C n -4-C n , n = 12, 14, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Strong acid-associated problems led to the investigation and use of weak organic acids as standalone stimulation fluids. This investigation concluded that acetic, citric, formic, and lactic acids can be efficiently used as alternatives to strong acids for situations where they are not recommended to be used such as shallow wells and high-temperature wells . However, the laboratory studies on some of these organic acids showed that precipitation of calcium salts made a noticeable impact on the diffusion of stimulation fluids inside the carbonate rocks, and this impact is clear at high temperature conditions. ,, Also, organic acids have limited solubility in water and cannot be used at high concentrations to avoid precipitations and damage related to these acids. , It is well-known that chemical solubility is one of the main parameters that control the applicability of any acid system.…”
Section: Introductionmentioning
confidence: 99%